Cloud Computing Technology for Efficient Water Resource Management: a Literature Survey - Chaskar, Snehal V; Solanki, PS; Khatarkar, PR (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is rapidly becoming an innovative and easy model for delivering the IT services along with dynamic infrastructure. Cloud computing uses Internet as communication media. It also transforming new idea to have centralized application and database servers. Water is a most essential resources and precious gift by nature on earth. It required in all fields viz. Industries, Agriculture, Irrigation, Domestic use, Plantation, Recreation, Wildlife etc. Water is in limited resource and required proper management. The advancement of Information and Communication Technology has significantly adopted for management of water resources. In this literature survey, we studied the work carried-out by the various researchers about the uses of cloud technology for water resource management.